β-carotene biotransformation to obtain aroma compounds - Uenojo,Mariana (2010)
Carotenoids are important constituents of food due to their color and because their degradation products generate important volatile compounds in foods. Aroma compounds derived from carotenoids are widely distributed in nature, and they are precursors of many important aromas in foods such as fruits and in flowers as well. They present high aromatic potential and are therefore of great interest to the industries of aromas and fragrances. In this study, more than 300 previously isolated microorganisms with potential for biotransformation of β-carotene present in the culture medium were selected using the plate method; about 80 strains presented capacity to produce aroma compounds and 7 strains were selected by an untrained panel of tasters to generate aroma compounds. The β-ionone was the main compound produced by CS1 (34.0 mg.L-1) and CF9 (42.4 mg.L-1) microorganisms at 72 and 24 hours of fermentation, cultured with and without pre-inoculation, respectively. The β-damascone and pseudoionone were found in low concentrations, 1,1,6-trimethyl-1,2,3,4-tetrahydronaphthalen (TTN) was tentatively identified and other compounds such as apocarotenoids, apparently obtained from the cleavage of the central part of the carotenoid, were detected.